Cell-Membrane-Coated Nanoparticles for Targeted Drug Delivery to the Brain for the Treatment of Neurological Diseases - Jianzhuang Li; Yanhao Wei; Chunlin Zhang; Rentang Bi; Yanmei Qiu; Yanan Li; Bo Hu (MDPI AG, 2023)
Neurological diseases (NDs) are a significant cause of disability and death in the global population. However, effective treatments still need to be improved for most NDs. In recent years, cell-membrane-coated nanoparticles (CMCNPs) as drug-targeting delivery systems have become a research hotspot. Such a membrane-derived, nano drug-delivery system not only contributes to avoiding immune clearance but also endows nanoparticles (NPs) with various cellular and functional mimicries. This review article first provides an overview of the function and mechanism of single/hybrid cell-membrane-derived NPs. Then, we highlight the application and safety of CMCNPs in NDs. Finally, we discuss the challenges and opportunities in the field.